THE GUIDING PRINCIPLES ON BUSINESS AND HUMAN RIGHTS: DIALEKTIKA KORPORASI DAN PEMENUHAN HAM - Yudha Akbar Pally (Sekretariat Jenderal DPR RI, 2013)
The international law has provided opportunity for the formulation of The Guiding Principles on Business and Human Rights that underlines corporation as the party securing an obligation and responsibility in respect for and enforcement of human rights today. In collaboration with long-firmly standing roles of the state, corporation has begun to map and direct their policies parallel in the framework of remedy of human rights violations offered by the Guiding Principles. This collaboration should be seriously undertaken by both corporation and the state. If not, the corporation will be punished through material and non-material loss and the state would face international sanctions.